Humanitarian Diplomacy for Indonesian Public Diplomacy in South East Asia - Christy Damayanti (Wacana Hukum, 2020)
Human values continue to experience developments in the dynamics of the international community. Indonesia is a country that has a concern for these human values. Many Indonesian diplomacy activities were carried out on the basis of human values, such as in the humanitarian diplomacy scheme. This study aims to look at the relationship between humanitarian diplomacy and Indonesian public diplomacy, especially in Southeast Asia. The method used in this research was descriptive qualitative with a literature study approach. The results showed that there was a positive contribution from the implementation of humanitarian diplomacy towards Indonesian public diplomacy. This positive value is seen from the presence of the governments of the countries in the Southeast Asia region towards Indonesia's foreign policy.